2022
DOI: 10.2174/18742106-v16-e2112271
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Oximetry and Three-Dimensional Analysis in Evaluating Immature Permanent Teeth Apexogenesis: Two Case Reports

Abstract: Background: Apexogenesis is a vital pulp therapy that aims to preserve pulp vitality and maintain root formation in not-fully-formed permanent teeth with exposed pulp from trauma or caries. To achieve success, reliable diagnostic tools are required to assess the pulp health and tooth development stage, design an appropriate treatment plan and evaluation, and follow-up. Pulse oximetry is a non-invasive method for monitoring pulp oxygen saturation, which corresponds to pulp vitality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…After 12 months, the results showed that the young permanent teeth exposed to two dental pulps after treatment with AC were asymptomatic, the pulp remained viable, and apical foramen were successfully induced. In addition, the oxygen level (oxygen saturation) in the pulpal blood supply in the AC group was tested via pulse oximetry within a normal range ( Figure 9 C) [ 100 ]. These experiments demonstrated that the use of AC as a capping material preserved pulp vitality, simultaneously induced root formation, and had the same tendency as MTA in the treatment results of partial pulpotomy, with lower costs compared to MTA.…”
Section: Advances In the Clinical Application Of Acmentioning
confidence: 99%
See 1 more Smart Citation
“…After 12 months, the results showed that the young permanent teeth exposed to two dental pulps after treatment with AC were asymptomatic, the pulp remained viable, and apical foramen were successfully induced. In addition, the oxygen level (oxygen saturation) in the pulpal blood supply in the AC group was tested via pulse oximetry within a normal range ( Figure 9 C) [ 100 ]. These experiments demonstrated that the use of AC as a capping material preserved pulp vitality, simultaneously induced root formation, and had the same tendency as MTA in the treatment results of partial pulpotomy, with lower costs compared to MTA.…”
Section: Advances In the Clinical Application Of Acmentioning
confidence: 99%
“…Role of AC in apexogenesis of immature permanent teeth. Radiographs ( a , b ) and 3D reconstruction images ( c , d ) showed that AC successfully promoted root development and reduced the apical foramen area in young permanent teeth [ 100 ]. ( D ).…”
Section: Advances In the Clinical Application Of Acmentioning
confidence: 99%
“…This technique outperforms other diagnostic techniques and evaluates the oxygen saturation in the blood supply of the tooth, a pivotal indicator of pulp vitality. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%